Hexokinase 2-mediated glycolysis supports inflammatory responses to Porphyromonas gingivalis in gingival fibroblasts - Wenqi Su; Jingwen Li; Lishan Jiang; Lang Lei; Houxuan Li (BMC, 2023)
Abstract Background When infected with Porphyromonas gingivalis, gingival fibroblasts undergo metabolic reprogramming, and rely on aerobic glycolysis rather than oxidative phosphorylation for rapid energy replenishment. Hexokinases (HKs) are catalysts for glucose metabolism, and HK2 constitutes the major HK inducible isoform. The objective of this study is to determine whether HK2-mediated glycolysis promotes inflammatory responses in inflamed gingiva. Methods Levels of glycolysis-related genes were assessed in normal and inflamed gingiva. Human gingival fibroblasts were harvested and infected with Porphyromonas gingivalis in order to mimic periodontal inflammation. 2-deoxy-d-glucose, an analogue of glucose, was used to block HK2-mediated glycolysis, while small interfering RNA was used to knock down HK2 expression. The mRNA and protein levels of genes were analyzed by real-time quantitative PCR and western blotting, respectively. HK2 activity and lactate production were assessed by ELISA. Cell proliferation was assessed by confocal microscopy. The generation of reactive oxygen species was assessed by flow cytometry. Results Elevated expression of HK2 and 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 was observed in the inflamed gingiva. P. gingivalis infection was shown to promote glycolysis in human gingival fibroblasts, as evidenced by increased gene transcription of HK2 and 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3, cell glucose consumption, and HK2 activity. Inhibition and knockdown of HK2 resulted in reduced cytokine production, cell proliferation, and reactive oxygen species generation. Furthermore, P. gingivalis infection activated the hypoxia-inducible factor-1α signaling pathway, thus promoting HK2-mediated glycolysis and proinflammatory responses. Conclusions HK2-mediated glycolysis promotes inflammatory responses in gingival tissues, and therefore glycolysis can be targeted in order to inhibit the progression of periodontal inflammation.